Characterization of polypropylene structural foams for large part applications - Esteves, F. R. (2013)
Structural foams (SF) consist of a sandwich-like material composed by a cellular core and a solid skin. It is the ideal material solution for injection moulding of short production series of large size parts. The injection moulding of SF is a low pressure process, thus it is a viable alternative for light moulding tools. The right formulation of structural foams and the use of adequate processing conditions are important to optimize the performance of the plastics part. In this study the processing conditions (injection speeds and percentages of mould filling) and the amount of chemical blowing agent (CBA) added to polypropylene were assessed on injection moulding circular discs. A hybrid mould with epoxy/aluminium composite cavity was used to produce the parts. The structural foam performance was evaluated by rheological, morphological and mechanical tests.